MODERN CONDITION AND DIRECT DEVELOPMENT OF WAREHOUSE LOGISTICS (International Journal of Innovative Technologies in Economy, 2023)
Warehouse logistics plays an increasingly important role in the activities of enterprises and modern society in general. Warehouses are used both by manufacturing enterprises to store raw materials, materials and products ready for shipment, and by trading companies that store finished products there. The optimality of the work of industrial enterprises, the speed of turnover in trading companies, as well as the level of customer satisfaction depend on the efficiency of warehouse management. To organize an effective business, you need to be able to properly manage resources, flows and means. The main element of warehouse logistics is a warehouse, the purpose of which in modern conditions is no longer the storage of goods, it is transformed into a transshipment point for the provision of modern services of cross-docking, assembly, consolidation, sorting, labeling of goods in order to minimize the costs of transportation and storage of goods and reducing delivery time. This article analyzes modern warehouse logistics management mechanisms and examines its main types. It was determined that the growth of the consumer society and the rapid development of electronic commerce require innovative solutions to ensure higher warehousing efficiency. The world and Ukrainian market of warehouse services and its growth rates were also analyzed. The impact of digital transformation on requirements for warehouse logistics management is determined. On the basis of the research carried out, directions for the development of warehouse logistics in the modern world were identified.